Enhanced Modified model for safe driving using Embedded Automotive control systems (International Journal of Engineering and Computer Science, 2014)
The population of our country has been increasing rapidly, which indirectly has increased the vehicle density and lead to many road accidents. The main causes of accidents include drowsiness of driver, health conditions, drunk and drive, collision of vehicles etc. The main aim of this project is to minimize the road accidents occurring due to driving fatigue which cause the loss of invaluable human life and other valuable things, till now we saw many ways to reduce causes for accidents,[1] we now implement a new concept of monitoring the driver’s health condition, by that we can avoid the accidents up to some extent, if the person met with any health issues the vehicle will get slow down/stopped and then the message will be sent to doctor for medical services using GSM, then by using GPS receiver the vehicle will be tracked to serve emergency medical services to the victim present inside the vehicle.